Natural history of malignant bone disease in hepatocellular carcinoma: final results of a multicenter bone metastasis survey. - Daniele Santini (Public Library of Science (PLoS), 2014)
Background Bone is an uncommon site of metastasis in patients with advanced hepatocellular carcinoma (HCC). Therefore, there are few studies concerning the natural history of bone metastasis in patients with HCC. Patients and methods Data on clinicopathology, survival, skeletal-related events (SREs), and bone-directed therapies for 211 deceased HCC patients with evidence of bone metastasis were statistically analyzed. Results The median age was 70 years; 172 patients were male (81.5%). The median overall survival was 19 months. The median time to the onset of bone metastasis was 13 months (22.2% at HCC diagnosis); 64.9% patients had multiple bone metastases. Spine was the most common site of bone metastasis (59.7%). Most of these lesions were osteolytic (82.4%); 88.5% of them were treated with zoledronic acid. At multivariate analysis, only the Child Score was significantly correlated with a shorter time to diagnosis of bone metastases (p = 0.001, HR = 1.819). The median survival from bone metastasis was 7 months. At multivariate analysis, HCC etiology (p = 0.005), ECOG performance status (p = 0.002) and treatment with bisphosphonate (p = 0.024) were associated with shorter survival after bone disease occurrence. The site of bone metastasis but not the number of bone lesions was associated with the survival from first skeletal related event (SRE) (p = 0.021) and OS (p = 0.001). Conclusions This study provides a significant improvement in the understanding the natural history of skeletal disease in HCC patients. An early and appropriate management of these patients is dramatically needed in order to avoid subsequent worsening of their quality of life.